General and Covid Anxiety: Observing the Outcome under Same Umbrella of Vaccination - Tehzeeb Zehra, Ammara Yousaf, Sehar Ashraf, Adil Mahmood, Rahila Aamir, Sarah Tayyab (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Despite of our strong want, the datum is that the Covid-19 pandemic is still not over. Its physical and mental sufferings are well known. Mass vaccination is the true hope to eradicate this virus. Despite of large scale efforts, vaccination including boosters still needs optimization Aim: To see the effect of vaccination against covid-19 on general and covid-19 related anxiety so to endorse the continuation of vaccination until the virus is completely eradicated. Study Design: Observational, cross-sectional study Place and Duration of Study: Shifa International Hospital Islamabad from 1st October 2021 to 31st March 2022. Methodology: Three hundred and thirteen subjects with recent history of Covid-19 vaccination were enrolled and 281 subjects completed the survey, asked to fill out CAS (covid-19 anxiety scale) and GAD-7 (general anxiety disorder) scale based on the recall of their feelings before vaccination and then about after vaccination. Results:. Majority were females (61.1%), had education graduation and above (71.2%), belonged to non-medical profession (71.4%). 47.3% had Covid-19 cases in family while 13.2% had covid-19 related deaths in family. Means of CAS were higher than the means of GAD-7 (p<0.001). Drop in anxiety level was statistically significant for both Covid related anxiety and general anxiety after vaccination (p<0.05). Conclusion: Vaccination against covid-19 is crucial to manage Covid related and general anxieties because, future covid waves hence the anxiety waves are still expected. Bereaved families need further psychiatric support beyond vaccination to deal with their anxieties. Keywords: Anxiety in covid, Vaccination and anxiety, Mental health in covid, Covid related anxiety